Community-based social determinants of three measures of mortality in Rhode Island cities and towns - Steven A. Cohen; Julia R. Broccoli; Mary L. Greaney (BMC, 2020)
Abstract Background Efforts to understand and address the causes of place-based health disparities have focused primarily on understanding the social determinants of health on a large geographic level, such as the region, state, or county. However, there is a growing need to assess and understand how place-based characteristics at smaller geographic areas relate to of local place-based neighborhood characteristics on population health. Therefore, the objective of this study was to evaluate the magnitude of the associations between social determinants of health and life expectancy (LE) and related measures on the community level. Methods LE at birth (LE0), remaining LE at age 65 (LE65), and age-specific mortality rates (ASMR) were calculated from mortality data (2009-2011) collected by the Rhode Island Department of Health (RIDoH) using abridged life table methods for each RI city/town. The city/town-specific LE and ASMR were linked to data collected by the US Census, RIDoH, the Federal Bureau of Investigation, and other databases that include information about multiple social, environmental, and demographic determinants of health. Bivariate correlations between city/town-level LE0, LE65, and ASMR and social determinants: demographics, household composition, income and poverty, education, environment, food insecurity, crime, transportation, and rural-urban status were examined. Results LE0 (range: 75.9-83.3 years) was strongly associated with the percent of the population with a graduate/professional degree (r = 0.687, p <  0.001), violent crime rate (r = − 0.598, p <  0.001), and per capita income (r = 0.553, p <  0.001). Similar results were observed for ASMR: ASMR was associated with the percent of the population with a graduate/professional degree (r = − 0.596, p <  0.001), violent crime rate (r = 0.450, p = 0.005), and per capita income (r = − 0.533, p < 0.001). The associations between LE65 and social determinants were more attenuated. Of note, none of the measures (LE0, LE65, or ASMR) were associated with any of the race/ethnicity variables. Conclusions There are several important place-based characteristics associated with mortality (LE and ASMR) among RI cities/towns. Additionally, some communities had unexpectedly high LE and low ASMR, despite poor social indicators.